Rapid and efficient optical tissue clearing for volumetric imaging of the intact and injured spinal cord in mice - Buxton, Andrew W.; Jalufka, Frank L.; Hruska, Margaret E.; Kubaney, Jack R.; McCreedy, Dylan A. (Frontiers in Neuroscience, 2025)
Tissue clearing and 3D imaging have emerged as powerful techniques to assess the cellular and tissue-level architecture of the spinal cord. With the rapidly increasing variety and complexity of optical tissue clearing techniques, there is a critical need for optimization and streamlining of tissue-specific protocols, particularly when dealing with injury or disease states. We evaluated and combined multiple organic solvent-based techniques to develop sciDISCO: a spinal cord injury-optimized DISCO tissue clearing protocol. sciDISCO allows for the robust clearing, labeling, and 3D imaging of the intact spinal cord, as well as clearing around and through the lesion site formed after contusive spinal cord injury. In addition, we have identified alternatives for hazardous chemicals commonly used in organic solvent-based clearing including dichloromethane and dibenzyl ether. In this study, we demonstrate the compatibility of sciDISCO with multiple different labeling techniques to provide robust analysis of unique neuronal populations and morphologies in addition to cellular and tissue-level changes occurring following spinal cord injury.